THE IMPACT OF DEBATE INSTRUCTION ON THE CRITICAL THINKING AND SPEAKING SKILLS OF 21ST CENTURY EFL STUDENTS - Khatimah, Khusnul; Aulia, Ade Annisa; Rahmawati, Yeni (Universitas Muhammadiyah Makassar, 2025)
In today’s rapidly evolving academic and technological environment, English learners are expected not only to master language skills but also to think critically and communicate effectively. However, many EFL instructional practices still focus heavily on memorization, leaving students underprepared for real-world communication demands. To address this gap, alternative teaching strategies that promote both reasoning and speaking performance are needed. This study investigates the impact of structured debate instruction on the speaking and critical thinking skills of EFL undergraduate students of Universitas Muhammadiyah Kalimantan Timur. Using a pre-experimental one-group pre-test and post-test design, 26 fourth-semester English education students participated in a five-meeting intervention. Their performances were assessed using rubrics adapted from the IELTS Speaking Band Descriptors and the Watson-Glaser Critical Thinking Appraisal framework. Data were analyzed using descriptive statistics, the Shapiro-Wilk test for normality, paired samples t-tests. The results showed significant improvement in both speaking and critical thinking skills (p .001). Among the rubric indicators, inference and fluency showed the highest post-test scores, while deduction and grammatical accuracy showed the lowest. These findings suggest that debate can be an effective pedagogical tool for enhancing spontaneous reasoning and communicative clarity in EFL settings, while also highlighting areas that may require additional support.